The twofold challenge for Karen Baptist intellectuals in colonial Burma: A national claim and its failure - Fujimura, Hitomi (Journal of Southeast Asian studies (Singapore), 2022)
Two years after the Anglo-Burmese War, with the British colonial takeover of Burma complete and yet still subject to outbreaks of rebellions, a small group of Karen Baptist intellectuals in Rangoon who formed the Karen National Association (KNA), attempted to assert a political claim to Karen nationhood. This article focuses on two letters, in English and Sgaw Karen, presented by Karen delegates on the occasion of the ceremony to celebrate the Golden Jubilee of Queen Victoria in 1887 in Rangoon, to investigate the colonial politics of loyalty and national claim. It argues that the letters were written for two different audiences, and by doing so the Karen Baptists were asserting dual claims; one directed at the British colonial authorities and the other, the wider population of Karen in Burma, with their multiple Karennic languages and religious and other affiliations. Both appeals failed to get the desired responses, however. This article then discusses the contradiction that this assertion of Karen nationhood alienated the Baptist leaders from their own diverse community.